Demographics and Histopathological Characteristics of Lung Cancer Patients in Cirebon District, Indonesia (2021-2023) - Syakira Puteri Sulaeman; Alya Amila Fitrie; Sedayu Sedayu (GHMJ (Global Health Management Journal))
Background: Based on the Global Burden of Cancer Study (GLOBOCAN) in 2020, In the world, lung cancer is the first cause of death. In Indonesia, lung cancer is the third highest.  Lung cancer is classified into two cell types: Small Cell Lung Cancer and Non-Small Cell Lung Cancer. There are two types of Non-Small Cell Lung Cancer: squamous cell carcinoma, adenocarcinoma, and large cell carcinoma.